2020
DOI: 10.21203/rs.3.rs-64855/v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Prevalence of readily detected amyloid blood clots in ‘unclotted’ Type 2 Diabetes Mellitus and COVID-19 plasma: A preliminary report

Abstract: Background: Type 2 Diabetes Mellitus (T2DM) is a well-known comorbidity to COVID-19 and coagulopathies are a common accompaniment to both T2DM and COVID-19. In addition, patients with COVID-19 are known to develop micro-clots within the lungs. The rapid detection of COVID-19 uses genotypic testing for the presence of SARS-Cov-2 virus in nasopharyngeal swabs, but it can have a poor sensitivity. A rapid, host-based physiological test that indicated clotting severity and the extent of clotting pathologies in the … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
2

Relationship

4
1

Authors

Journals

citations
Cited by 6 publications
(19 citation statements)
references
References 43 publications
2
17
0
Order By: Relevance
“…Previously we have shown that naïve PPP (exposed to ThT) from healthy individuals and T2DM, have significantly less anomalous clotlets, compared to acute COVID-19 PPP (Pretorius et al, 2020). Here we show that PPP from Long COVID/PASC samples also have considerable anomalous (amyloid) clotlets, similar to that of acute COVID-19 PPP samples.…”
Section: Platelet Poor Plasma (Ppp): Amyloid Protein and Anomalous Clotting In Platelet Poor Plasma Samples Before And After Two Trypsin supporting
confidence: 63%
See 2 more Smart Citations
“…Previously we have shown that naïve PPP (exposed to ThT) from healthy individuals and T2DM, have significantly less anomalous clotlets, compared to acute COVID-19 PPP (Pretorius et al, 2020). Here we show that PPP from Long COVID/PASC samples also have considerable anomalous (amyloid) clotlets, similar to that of acute COVID-19 PPP samples.…”
Section: Platelet Poor Plasma (Ppp): Amyloid Protein and Anomalous Clotting In Platelet Poor Plasma Samples Before And After Two Trypsin supporting
confidence: 63%
“…In the current study, we investigate if the lingering symptoms that individuals with Long COVID/PASC might be due to the presence of persistent circulating plasma clots that are resistant to fibrinolysis. We have previously shown that large anomalous (amyloid) fibrin(ogen) deposits are present in plasma from acute COVID-19 patients (Pretorius et al, 2020. Here we show that plasma samples from Long COVID/PASC still contain large anomalous (amyloid) deposits, and that these deposits are most resistant to fibrinolysis, even with the treatment of a two-step trypsin method.…”
Section: Introductionmentioning
confidence: 50%
See 1 more Smart Citation
“…However, SARS-CoV-2 also secretes products/proteins that modulate blood clotting cascades ( Eslamifar et al, 2020 ). Pretorius et al (2020a , b , 2021) identified fibrinolytic resistant amyloid microclots in COVID-19 plasma ( Figure 4 ) and in plasma samples collected from 11 PASC subjects. This suggests that patients who suffer from both issues/insults might be disproportionally impacted by PASC symptoms that could result from blood inflammatory/coagulation cascades.…”
Section: Microbiome Dysbiosis Can Disrupt Host Metabolic and Neuroendocrine Signaling And/or Epithelial Barrier Functionmentioning
confidence: 98%
“…COVID-19 is associated with a profound escalation in clotting cascades ( Grobler et al, 2020 ) including an amyloid form of fibrin that may be associated with infection-related systemic inflammatory conditions ( Esposito et al, 2016 ; Pretorius et al, 2020b ). This may affect the meninges, the three membrane layers surrounding the central nervous system.…”
Section: Sars-cov-2 And/or Related Inflammatory Insults May Disrupt Brainstem Signalingmentioning
confidence: 99%